Mechanical design study of drive mechanism of initial study of drag characteristics of the drogue parachute on leatjet 24D - Ismail, Muhammad Arif; Rosly, Nurhayati (FAZ Publishing, 2019)
The title of my project is Drag Characteristic of the Drogue Parachute on Learjet 24D. The purpose of my study was to adding a drogue parachute on Learjet 24D as an additional braking device. There are 4 types of parachutes, it is Solid Textile Parachute, Slotted Textile Parachute, Rotating Parachute and Gliding Parachute. Each of the type has different design, which has different uses. Based from the entire parachute, only 2 has been chosen for final testing. All of the chosen parachute will be drawn using SolidWorks software and will be import to Ansys software to be run and getting the data. Based from the data obtained, all of the chosen parachute will be compare and only one drogue parachute will be choose to install on aircraft Learjet 24D. This study is purposely to reduce the rate of slowing down for Learjet24D during landing segment and determine the braking impact occurs.